Health Professionals of Prevention in Italy: The Value of Expertise During COVID-19 Pandemic - Wachocka, Malgorzata; Pattavina, Fabio; Palluzzi, Vincenzo; Cerabona, Vito; Laurenti, Patrizia (Frontiers in Public Health, 2020)
There are 22 different degree courses related to the Healthcare Professions in the Italian university system, which are divided into four areas. "Healthcare Professions of Prevention" is the fourth area and it is fundamental for the National Health Service. In particular, in this pandemic emergency situation, the contribution of the Prevention Technicians in the Environment and Workplaces (PTEW) is essential in the field and workplace management. The "Core Competence" of the PTEW is to carry out, with professional autonomy, prevention, verification and control activities in the field of hygiene and safety of living and working environments. In the hospitals, the indications provided by national and/or regional authorities are implemented through procedures on good hygiene practices developed by PTEW (e.g. hand hygiene, "respiratory tract hygiene", environmental hygiene, social distancing and use of Personal Protective Equipment). One of the activities is the health surveillance on the field by population monitoring. The protocols foreseen for the "in-flow of workers" involve a wider control between social life and work. The PTEW will use a Check List divided into 3 macro phases: Entry, Activity Context and Exit, defining each behaviour of the work phases with a constant presence of verification of the procedures. The PTEW will be a Leader on the topics of education, training and persuasion, considering a New Principle that "transforms the worker as active part in the application and diffusion of the safety measures”.